2022
DOI: 10.1101/2022.08.30.22279087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of a Ketogenic and Low Fat Diet on the Human Metabolome, Microbiome and Food-ome in Adults at Risk for Alzheimer’s Disease

Abstract: INTRODUCTION: The ketogenic diet (KD) is an intriguing candidate for neuroprotection in Alzheimer's disease (AD) given its protective effects against metabolic dysregulation and seizures. The diet's neuroprotective effects have been shown to be gut microbiome-dependent in mice; thus we examined KD-induced changes in the gut microbiome and metabolome in patients at-risk for AD. METHODS: We compared the low-carbohydrate modified Mediterranean Ketogenic Diet (MMKD) to the low-fat American Heart Association D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We utilized a Negative Binomial Linear Mixed Effect model to ensure that our statistics agreed with our study design; we modeled time, dietary sequence (whether MMKD intervention was first or second), cognitive status, and diet (whether a given individual was on MMKD or AHAD at a given time point) as fixed effects while subject identity was modeled as a random effect. Microbes, food features, and metabolites were ordered by the log-ratio of their relative abundances in objectively normal cognition to mild cognitive impairment or MMKD to AHAD individuals, respectively 92,93 and the top and bottom ten features were examined more closely 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We utilized a Negative Binomial Linear Mixed Effect model to ensure that our statistics agreed with our study design; we modeled time, dietary sequence (whether MMKD intervention was first or second), cognitive status, and diet (whether a given individual was on MMKD or AHAD at a given time point) as fixed effects while subject identity was modeled as a random effect. Microbes, food features, and metabolites were ordered by the log-ratio of their relative abundances in objectively normal cognition to mild cognitive impairment or MMKD to AHAD individuals, respectively 92,93 and the top and bottom ten features were examined more closely 21 .…”
Section: Methodsmentioning
confidence: 99%
“…We used samples from a randomized crossover pilot trial of a Modified Mediterranean-Ketogenic Diet (MMKD) or the American Heart Association Diet (AHAD) ( Figure 1 ) in a cohort of prediabetic participants that were either mildly cognitively impaired (MCI, n = 9) or cognitively normal (CN, n = 10) 20 . In a series of studies using the same cohort, we previously found that MMKD leads to increased Aβ42 and decreased tau in CSF 20 , changes in the gut microbiome 21 , and reversal of serum-based AD-associated lipid signature 25 . In the current study, we broaden the scope of blood biomarkers by using an NMR-metabolomics platform that measured amino acids, ketone bodies, triglycerides, and lipoprotein levels and lipoprotein composition.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation